1999
DOI: 10.1017/s1355838299981396
|View full text |Cite
|
Sign up to set email alerts
|

The identification and characterization of a novel splicing protein, Isy1p, of Saccharomyces cerevisiae

Abstract: We have identified a novel splicing factor, Isy1p, through two-hybrid screens for interacting proteins involved in nuclear pre-mRNA splicing. Isy1p was tagged and demonstrated to be part of the splicing machinery, associated with spliceosomes throughout the splicing reactions. At least a portion of the Isy1 protein population is associated with snRNAs; low levels of U5 and U6 snRNAs are coimmunoprecipitated specifically with Isy1p. When the ISY1 gene was knocked out, no defect in vegetative growth was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…2A, lower panel), which encodes a component of the Prp19 complex that functions during the catalytic steps in splicing. [57][58][59] In contrast, jhd1D displays mild positive genetic interactions with both ist3D and isy1D (Fig. 2B).…”
Section: Resultsmentioning
confidence: 94%
“…2A, lower panel), which encodes a component of the Prp19 complex that functions during the catalytic steps in splicing. [57][58][59] In contrast, jhd1D displays mild positive genetic interactions with both ist3D and isy1D (Fig. 2B).…”
Section: Resultsmentioning
confidence: 94%
“…To investigate the association of the Syf proteins with spliceosomal snRNAs, the same extracts (but without ATP or substrate pre-mRNA, i+e+, without spliceosome assembly) were incubated with IgG and the presence of spliceosomal snRNAs in the immunoprecipitates was investigated by Northern blot analysis (Fig+ 5)+ AntiPrp8 antibodies, which efficiently immunoprecipitate U5 snRNPs, as well as U4/U6+U5 tri-snRNP complexes (Teigelkamp et al+, 1995), were used as a control (Fig+ 5, lanes 2, 5, 8, and 11)+ Under standard immunoprecipitation conditions (150 mM salt), IgG precipitated low amounts of U5 and U6 snRNAs along with ProtASyf1p, Prot+A-Syf2p (the U5 was only just detectable), and Prot+A-Syf3p (Fig+ 5, lanes 7, 10, and 13, respectively)+ (The U2 seen in lane 13 was also coimmunoprecipitated with Prp8p, and so is either nonspecific, or represents a complex containing at least the U2 and U5 snRNPs+) Under less stringent conditions (100 mM salt), U4 snRNA was also coprecipitated with ProtASyf1p and Prot+A-Syf3p (Fig+ 6, lanes 16 and 20), indicating a possible association with salt-sensitive trisnRNP complex+ In summary, we have shown that Syf1p, Syf2p, and Syf3p are stably associated with spliceosomes during both steps of the splicing reaction, and interact either partially or transiently with U5 and U6 snRNPs+ Similar observations were made for Isy1 protein (Dix et al+, 1999)+ Like Syf2p, Isy1p is a small protein that is dispensable for cell viability and interacts with spliceosomes, but is not essential for the splicing reaction; however, it is required for the efficient splicing of certain substrates (Dix et al+, 1999)+ A similar role is possible for Syf2p, although no effect has been found with the introns tested so far+ Results from exhaustive twohybrid screens have demonstrated interactions of both Syf2p and Isy1p with Syf1p, Syf3p, and another splicing factor, Cef1p (Dix et al+, 1999;Ben-Yehuda et al+, 2000a)+ Therefore, these two small proteins may act as mediators that strengthen interactions between these splicing factors, and possibly other proteins+ Like Isy1p, the Syf1, Syf2, and Syf3 proteins coprecipitate low levels FIGURE 3. Depletion of Syf1p or Syf3p results in accumulation of unspliced RNA+ RNA was extracted from CAZY4 cells (P MET3 -HA-SYF1) grown for 12 h under Syf1-expressing conditions (minimal dropout medium lacking methionine; lane 1) or Syf1-repressing conditions (plus 5 mM methionine; lane 2), from SB74 cells (P TET -HA-SYF3 ) grown for 12 h in YPDA without or with 50 g/mL tetracycline (lanes 4 and 5, respectively), and from wild-type (BMA38a) cells grown with 5 mM methionine (lane 3) or with 50 mg/mL tetracycline (lane 6)+ Primer extension analysis was performed to measure the levels of unspliced pre-U3A and pre-U3B transcripts and, as a control, of intronless U1 snRNA+ FIGURE 4.…”
Section: Syf1p Syf2p and Syf3p Associate With Spliceosomesmentioning
confidence: 80%
“…Depletion of Syf1p or Syf3p results in accumulation of unspliced RNA+ RNA was extracted from CAZY4 cells (P MET3 -HA-SYF1) grown for 12 h under Syf1-expressing conditions (minimal dropout medium lacking methionine; lane 1) or Syf1-repressing conditions (plus 5 mM methionine; lane 2), from SB74 cells (P TET -HA-SYF3 ) grown for 12 h in YPDA without or with 50 g/mL tetracycline (lanes 4 and 5, respectively), and from wild-type (BMA38a) cells grown with 5 mM methionine (lane 3) or with 50 mg/mL tetracycline (lane 6)+ Primer extension analysis was performed to measure the levels of unspliced pre-U3A and pre-U3B transcripts and, as a control, of intronless U1 snRNA+ FIGURE 4. Coprecipitation of spliceosomes with protein A-tagged Syf1p, Syf2p, and Syf3p+ Splicing reactions (25:l) were performed with radiolabeled actin pre-mRNA and extracts from cells producing protein A-tagged Syf1 (Prot+A-Syf1p; lanes 4-6), Prot+A-Syf2p (lanes 7-9), Prot+A-Syf3p (lanes 10-12), or unfused protein A (Prot+A-vector; lanes 1-3)+ After 20 min of incubation under splicing conditions, the samples were incubated with anti-Prp8 antibodies and protein A-Sepharose beads (lanes 1, 4, 7, 10), with IgG-agarose beads (lanes 3, 6, 9, 12) or, as a control, with agarose beads alone (lanes 2, 5, 8, 11)+ RNAs in the precipitates RNA were analyzed in a 6% (w/v) polyacrylamide-8 M urea gel followed by autoradiography+ The positions of pre-mRNA, exon 1 (Ex1), lariat intron-exon 2 (IVS-Ex2), spliced exons (mRNA) and excised lariat intron (IVS) are indicated+ of U5 and U6 spliceosomal snRNAs+ As proposed for Isy1p (Dix et al+, 1999), this may indicate an association of these proteins with a product of dissociating tri-snRNPs or spliceosomes+ The coprecipitation of U4 snRNA with Syf1p and Syf3p under less stringent conditions (100 mM salt) is compatible with this being a salt-sensitive complex in which the U4 and U6 snRNAs are not stably base paired+ Chung et al+ (1999) showed that the Syf3/Clf1 protein was required for spliceosome assembly, specifically for the productive association of the U4/U6+U5 tri-snRNP particle to the U1/U2-containing pre-spliceosome+ They proposed that it may act as a scaffold protein during spliceosome assembly, promoting U4/U6+U5 particle addition to the pre-spliceosome+ These authors did not detect any snRNA association with an HA-tagged Clf1p; however, our experience with the HA-tagged Syf proteins indicated that the much smaller HA epitope may be masked in the complexes+ As low levels of U5 and U6 snRNAs are found associated with Syf1p, Syf2p, Syf3p (this work), and Isy1p (Dix et al+, 1999) and these proteins interact with each other (Dix et al+, 1999;BenYehuda et al+, 2000a), it seems plausible that, after promoting the assembly of the U4/U6+U5 particle into the spliceosome, the proteins remain associated with the U5 and U6 snRNAs following disruption of the base-pairing between U4 and U6, and they are detected in a transient postsplicing U5/U6 particle that results from spliceosome disassembly+…”
Section: Syf1p Syf2p and Syf3p Associate With Spliceosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…SNT304 and SNT384 were found to correspond to ORFs YJR050w and YBR188c, respectively. YJR050w was recently reported by twohybrid screening to be Isy1p as a protein interacting with Syf1p (20). It is a protein of 235 amino acid residues with a calculated molecular weight of 28,024.…”
Section: Resultsmentioning
confidence: 99%